Prosumer: o novo protagonista da comunicação - Bório, Pâmela Monique Cardoso (2014)
This research discusses communication postmodern, new habits of consumption and production of information and the emergence of the prosumer, the protagonist in this process. The term was coined by Alvin Toffler (1995) to describe the new profile producer-consumer. The prosumer can be compared to the producer of the era that predates capitalism, but now reappears as a producer of information media, strong and influential, actively participating in the preparation of informative content on various new media: Internet and Digital TV - iDTV. Professional journalists are having to reinvent themselves. The audience is no longer passive. Marketers seek to understand the mechanisms and consumer trends in new media. The audiovisual industry has been adapting to the new era of the popularization of the Internet and the continued growth of social networking. As the production of the prosumer is being exploited on the Internet, on television and in iDTV? Which direction the phenomenon designed to communicate? What are the current trends? The overall goal of this research is to show the overlap of the prosumer with the audiovisual media industry and try to understand the role that public in everyday communication. As a result of this research, we can say that the performance of the prosumer, although it is something recent, already produces effects in the history of mankind. Understanding this issue is to involve oneself in order cosnciente dynamic information society in which most cultures are embedded.